The Impact of the Glycoprotein Ia Collagen Receptor Subunit A1648G Gene Polymorphism on Coronary Artery Disease and Acute Myocardial Infarction - Kroll, Hartmut; Gardemann, Andreas; Fechter, Andreas; Haberbosch, Werner; Santoso, Sentot (Thrombosis and Haemostasis, 2000)
Platelet glycoprotein (GP) Ia is the major receptor for collagen and plays an important role in platelet adhesion and aggregation. Different gene polymorphisms have been identified that induce either various expression levels (C807T) or alterations of the tertiary structure (A1648G) of GPIa. Previously, we could demonstrate an association of the GPIa C807T dimorphism with nonfatal myocardial infarction. We have now analysed the influence of the GPIa A1648G (Br, HPA-5) dimorphism on the risk of coronary artery disease (CAD) and acute myocardial infarction (AMI). DNA samples from 2163 male Caucasian patients who underwent coronary angiography were genotyped by polymerase chain reaction and restriction fragment length analysis. The relation of the GPIa A1648G dimorphism to the extent of CAD was determined by multiple regression analysis with adjustment for coronary risk factors. Odds ratios (OR) as an estimate of relative risk of CAD and AMI and two-tailed p-values were calculated by multiple logistic regression. In the total study sample, no association was detected between the A1648G dimorphism and CAD or AMI. However, upon analysis of low-risk patient subgroups we found an association of the GPIa A1648G polymorphism with the risk and the extent of CAD (patients with high apoAI/apoB ratio: OR 0.59, p = 0.0090; nonand ex-smokers: OR 0.66, p = 0.0131; both inclusion criteria: OR 0.44, p = 0.0003). The relative frequency of the A1648 allele was higher in controls whereas the GG1648 genotype was overrepresented in patients with CAD. This association was also detectable when individuals with low expression levels of GPIa (C807 homozygotes) were analysed (patients with high apoAI/apoB ratio: OR 0.44, p = 0.0045; nonand ex-smokers: OR 0.61, p = 0.0370). Our findings indicate that the A1648G polymorphism of the platelet collagen receptor plays a role in CAD in well defined patient groups.
Keywords: Glycoprotein Ia/IIa; α2β1integrin; risk factor; myocardial infarction; human platelet alloantigen Bra/Brb (HPA-5b/a)